2011
DOI: 10.1111/j.1748-3743.2011.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of descriptive studies that investigated associated factors with the management of incontinence in older people in care homes

Abstract: Older people and their families should be involved with decisions regarding their preferred care, goals, management and outcomes for managing incontinence, promoting or maintaining continence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 57 publications
1
33
0
1
Order By: Relevance
“…40e44 Other studies that have looked at implementation of interventions for other purposes in care home settings have identified the importance of involving family members in decision-making in the successful management of behavioral problems 45 and the management of incontinence. 46 A systematic review of the implementation of psychosocial interventions for people with dementia in care homes found that active engagement of care-home staff and family members played a crucial role in successful implementation. 47 Similarly, systematic reviews on the more general topic of improving prescribing practice in care homes 48e53 also have been unable to make clear recommendations for future practice due to the varied nature of the design, interventions, outcomes, and results 49,50,53 and the poor quality of included studies.…”
Section: Results In Contextmentioning
confidence: 99%
“…40e44 Other studies that have looked at implementation of interventions for other purposes in care home settings have identified the importance of involving family members in decision-making in the successful management of behavioral problems 45 and the management of incontinence. 46 A systematic review of the implementation of psychosocial interventions for people with dementia in care homes found that active engagement of care-home staff and family members played a crucial role in successful implementation. 47 Similarly, systematic reviews on the more general topic of improving prescribing practice in care homes 48e53 also have been unable to make clear recommendations for future practice due to the varied nature of the design, interventions, outcomes, and results 49,50,53 and the poor quality of included studies.…”
Section: Results In Contextmentioning
confidence: 99%
“…Until now, little data have been collected in Europe with regard to incontinence care in nursing homes and most existing studies have been conducted in the USA (Roe et al . ). The result of this study provides an initial insight into the quality of incontinence care with respect to structural, process level and outcome indicators in Austrian nursing homes.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the morbidity associated with UI in older people, its presence with co-existent dementia increases the likelihood of institutionalization [9]. Unfortunately, once present, there is evidence of institutional practices making incontinence more likely [10]. Likewise, caregivers identify looking after an older person with dementia and incontinence as being burdensome [11,12].…”
Section: Introductionmentioning
confidence: 99%